Vectorial transport of enalapril by Oatp1a1/Mrp2 and OATP1B1 and OATP1B3/MRP2 in rat and human livers - Liu, Lichuan; Keppler, Dietrich (The journal of pharmacology and experimental therapeutics, 2006)
Although Oatp1a1 (rat organic anion-transporting polypeptide 1a1) was the transporter found responsible for the hepatocellular entry of enalapril (EN) into the rat liver, the canalicular transporter involved for excretion of EN and the metabolite, enalaprilat (ENA), was unknown. The Eisai hyperbilirubinemic rat (EHBR) that lacks Mrp2 (multidrug resistance-associated protein 2) was used to appraise the role of Mrp2 in the excretion of [3H]EN and its metabolite [3H]ENA in single-pass rat liver preparations. Although the total and metabolic clearances and hepatic extraction ratios at steady-state were virtually unaltered for EN in EHBR compared with published values of Sprague-Dawley rats, the biliary clearances of EN and ENA were significantly reduced almost to zero (P < 0.05). Involvement of human OATP1B1, OATP1B3, and MRP2 in EN transport was further assessed in single- or double-transfected mammalian cells. Human embryonic kidney 293 cells that expressed OATP1B1 or OATP1B3 showed that OATP1B3 transport of EN (20-500 μM) was of low affinity, whereas transport of EN by OATP1B1 was associated with the Km of 262 ± 35 μM, a value similar to that for Oatp1a1 (214 μM). The transcellular transport of EN via human OATP1B1 and MRP2, investigated with the double-transfected Madin-Darby canine kidney (MDCK) II cells in the Transwell system, showed that the sinusoidal to canalicular flux of EN in the OATP1B1/MRP2/MDCK cells was significantly higher (P < 0.05) than that of mock/MDCK and OATP1B1/MDCK cells. EN was transported by Oatp1a1 and Mrp2 in rats and OATP1B1/OATP1B3 and MRP2 in humans.